ANALISIS PENGENDALIAN KUALITAS PRODUKSI DENGAN METODE STATISTICAL PROCESS CONTROL (SPC) PADA PT. MEDIA HALUAN MANDIR - Dita Noviyani; Restu Restu; Anggia Paramitha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research is conducted to know the implementation and quality control on the company’s production process, seen from the final product that produced. The purpose is to reduce defective product by identifying the factors that cause the damage and provide suggestions for improvement. PT. Media Haluan Mandiri is a company that engaged in the printing and publishing sector. The company sets a target defective product shouldn’t be more than 3 percent from production amount. But in reality there are still more than 3 percent production. Statistical Process Control (SPC) is used for the quality control, which has seven assistive tools: check sheet, scatter diagram, cause and effect diagram, pareto diagram, flow chart, histogram, and control chart. The results shows the type of damage that occurred is shaded as much as 3,025 copies, filthy newspaper as much as 6,994 copies and blurred ink as much as 5,458 copies. On the control chart, there is a fluctuating point and it’s out of control. There is a positive relationship between the amount of production with the amount of defective products with the highest level of damage is filthy newspaper of 45.19 percent, blurred ink of 39.27 percent and shaded of 19.55 percent. Factors causing the damage are human, machine, materials, method, environment, and measurement. Based on the results of research at PT. Media Haluan Mandiri, the company needs to take prevention and corrective action such as consider the condition of the operator at work, reguler maintenance on the machine, and selecting tight material received from suppliers. Through these actions, defective product expected to be minimized and the quality of the company's products expected to be improved.Keywords : quality control, statistical process control, and defective product.